1994
DOI: 10.3758/bf03211667
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor synchronization: Motor responses to pseudoregular auditory patterns

Abstract: Musically trained and untrained subjects (N = 30) were asked to synchronize their finger tapping with stimuli in auditory patterns. Each pattern comprised six successive tonal stimuli of the same duration, the first of which was accented by a different frequency. The duration of interstimulus onset intervals (ISIs) gradually increased or decreased in constant steps toward the end of the patterns. Four values of such steps were used in different trials: 20, 30, 45, and 60 msec. Various time-control mechanisms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The suggestion that produced time intervals are based on previous intervals rather than on an internal clock corresponds intuitively better to the flexibility of human timing, as is known from music, sports, and everyday activities, in which adjustment to temporal change can be both rapid and accurate. This flexibility includes acting and responding to continuously changing intervals (Collier and Wright 1995;Franek et al 1994;Madison 2000a), a type of performance for which an intrinsically isochronous open-loop mechanism would seem unsuitable.…”
Section: Discussionmentioning
confidence: 99%
“…The suggestion that produced time intervals are based on previous intervals rather than on an internal clock corresponds intuitively better to the flexibility of human timing, as is known from music, sports, and everyday activities, in which adjustment to temporal change can be both rapid and accurate. This flexibility includes acting and responding to continuously changing intervals (Collier and Wright 1995;Franek et al 1994;Madison 2000a), a type of performance for which an intrinsically isochronous open-loop mechanism would seem unsuitable.…”
Section: Discussionmentioning
confidence: 99%
“…We tested a group of musicians. In studies of timing, the performance of musicians has been compared with that of non-musicians, with the result that musicians often perform better overall (Billon and Semjen 1995;Franek et al 1991Franek et al , 1994Kincaid et al 2002). On the basis of previous work one might expect musicians, as compared to non-musicians, to show superior ability in judging temporal order.…”
Section: Methodsmentioning
confidence: 99%
“…Michon (1967) used linear changes in IOI duration and found that participants adjusted their ITIs in a stepwise fashion, suggesting that they waited to adjust their internal timekeeper period until a tempo change was detectable and relied on phase correction between period adjustments. This strategy was not evident in other studies, however, in which either very short sequences (Franek, Mates, Radil, Beck, & Pöppel, 1994) or very gradual tempo changes (Madison & Merker, 2005) were used. Data from another recent study (Schulze et al, 2005), however, are suggestive in that regard.…”
Section: Global Perturbationsmentioning
confidence: 99%